Green Trends in the Hotel Industry - Status and Opportunities of SERBIA - Muhi, Bela Muhi; Stanković, Jasmina; Jovanović, Dušan; B. Božović, Rade (Journal of Economic Development, Environment and People, 2013)
So-called "green" hotels that are trying to respect the rules of environmental pollution and reduce it to a minimum have become wide spread recently. The main principle of this trend is to use a variety of methods of responsible hotel operations, to reduce energy, water consumption and carbon dioxide emissions, to take care of the decomposition of solid waste and increase the recycling of waste materials, to use conventional detergents and other chemical agents to the lower measure and replace it by harmless "organic", to prevent or at least reduce the pollution of the environment and, wherever possible to preserve local biodiversity. In this paper, the authors provide an overview of green trends in the hotel industry with a focus on status and opportunities in Serbia.